The relationship between fat mass and obesity associated gene polymorphism rs9939609 and resting cerebral blood flow in a midlife sample with overweight and obesity - Stillman, Chelsea M.; Jakicic, John M.; Rogers, Renee J.; Roecklein, Kathryn A.; Barrett, Grant; Kang, Chaeryon; Erickson, Kirk I. (Frontiers in Human Neuroscience, 2022)
BACKGROUND: The single nucleotide polymorphism (SNP) rs9939609 in the fat mass and obesity associated FTO gene has been linked with increased BMI in adults. Higher BMI has been associated with poor brain health and may exert deleterious effects on neurocognitive health through cerebral hypoperfusion. However, it is unclear whether there is a relationship between the FTO genotype and cerebral perfusion or whether FTO genotype moderates the effects of weight loss on cerebral perfusion. Using data from a randomized controlled behavioral weight loss trial in adults with overweight and obesity, we tested (1) whether carriers of the A allele for FTO rs9939609 demonstrate reduced resting cerebral blood flow (rCBF) as compared to T carriers, and (2) whether the FTO genotype moderates the effects of weight loss on rCBF. We hypothesized that carriers of the A allele would exhibit lower resting CBF in frontal brain areas compared to T/T homozygotes at baseline, and that intervention-induced weight loss may partially remediate these differences. METHODS AND RESULTS: One hundred and five adults (75.2% female, mean age 44.9 years) with overweight or obesity were included in the analyses. A resting pseudo-continuous arterial spin labeling scan was acquired to examine rCBF. Age, sex, and BMI were included as covariates. At baseline, A carriers had greater rCBF in a diffuse cluster extending into the brainstem, motor cortex, and occipital lobe, but lower perfusion in the temporal lobe. We found no evidence that FTO moderated the effect of the intervention group assignment on rCBF changes. CONCLUSIONS: Overall, these results indicate that (a) individual variation in rCBF within a sample with overweight and obesity may be attributed to a common FTO variant, but (b) a weight loss intervention is effective at increasing rCBF, regardless of FTO genotype.